Clade 8 and clade 6 strains of Escherichia coli O157:H7 from cattle in Argentina have hypervirulent-like phenotypes - Amigo, Natalia (2015)
The hemolytic uremic syndrome (HUS) whose main causative agent is enterohemorrhagic Escherichia coli (EHEC) O157:H7 is a disease that mainly affects children under 5 years of age. Argentina is the country with the highest incidence of HUS in the world. Cattle are a major reservoir and source of infection with E. coli O157:H7. To date, the epidemiological factors that contribute to its prevalence are poorly understood. Single nucleotide polymorphism (SNP) typing has helped to define nine E. coli O157:H7 clades and the clade 8 strains were associated with most of the cases of severe disease. In this study, eight randomly selected isolates of EHEC O157:H7 from cattle in Argentina were studied as well as two human isolates. Four of them were classified as clade 8 through the screening for 23 SNPs; the two human isolates grouped in this clade as well, while two strains were closely related to strains representing clade 6. To assess the pathogenicity of these strains, we assayed correlates of virulence. Shiga toxin production was determined by an ELISA kit. Four strains were high producers and one of these strains that belonged to a novel genotype showed high verocytotoxic activity in cultured cells. Also, these clade 8 and 6 strains showed high RBC lysis and adherence to epithelial cells. One of the clade 6 strains showed stronger inhibition of normal water absorption than E. coli O157:H7 EDL933 in human colonic explants. In addition, two of the strains showing high levels of Stx2 production and RBC lysis activity were associated with lethality and uremia in a mouse model. Consequently, circulation of such strains in cattle may partially contribute to the high incidence of HUS in Argentina.